X-ray/gamma radiation shielding properties of Aluminium-BariumZinc Oxide nanoparticles synthesized via low temperature solution combustion method - K.V. Sathish; K.N. Sridhar; L. Seenappa; H.C. Manjunatha; Y.S. Vidya; B. Chinnappa Reddy; S. Manjunatha; A.N. Santhosh; R. Munirathnam; Alfred Cecil Raj; P.S. Damodara Gupta; B.M. Sankarshan (Nuclear Engineering and Technology, 2023)
For the first time Aluminium-BariumZinc oxide nanocomposite (ZABONC) was synthesized by solution combustion method where calcination was carried out at low temperatures (6000C) to study the electromagnetic (EM) (X/γ) radiation shielding properties. Further for characterization purpose standard techniques like PXRD, SEM, UV-VISIBLE, FTIR were used to find phase purity, functional groups, surface morphology, and to do structural analysis and energy band gap determination. The PXRD pattern shows (hkl) planes corresponding to spinel cubic phase of ZnAl2O4, cubic Ba(NO3)2, α and γ phase of Al2O3 which clearly confirms the formation of complex nano composite. From SEM histogram mean size of nano particles was calculated and is in the order of 17 nm. Wood and Tauc’s relation direct energy band gap calculation gives energy gap of 2.9 eV. In addition, EM (X/γ) shielding properties were measured and compared with the theoretical ones using standard procedures (NaI (Tl) detector and multi channel analyzer MCA). For energy above 356 keV the measured shielding parameters agree well with the theory, while below this value slight deviation is observed, due to the influence of atomic/crystallite size of the ZABONC. Hence synthesized ZABONC can be used as a shielding material in EM (X/γ) radiation shielding.